PENGARUH PERILAKU SANITASI MASYARAKAT DESA SUMBERPORONG TERHADAP KUALITAS AIR SUNGAI WELANG - Andiyansya, Moch. Farid; Jamil, Achmad Maulana Malik; Ni’matullah, Onik Farida (Social Landscape Journal, 2025)
Human activities have created environmental difficulties in the Welang River. The actions at issue here constitute pollution, namely related to the disposal of household waste and the usage of toilets. Environmental disorders including ARI, TB, dengue fever, malaria, worms, and skin ailments are caused by this circumstance. In order to understand how sanitation efforts affect water quality and to forestall the development of more complicated issues, it is crucial to examine the existing quality level of the river water in Welang. This descriptive research included both quantitative and qualitative methodologies. This study compares the findings with PP No. 22 of 2021 in an effort to determine how sanitation operations have affected the Welang River's water quality. Analyses conducted in accordance with PP. No. 22 of 2021 have shown that the Welang River's water quality remains appropriate. Nevertheless, despite the lack of cleanliness initiatives, this pollution has taken place.